Edukasi Kosmetika Aman: Upaya Meningkatkan Pengetahuan Warga Gampong Kopelma Darussalam - Maryam, Siti; Isnaini, Nadia; Prajaputra, Vicky; Ulfa, Safra; Raihanylkhairi (Universitas Mataram, 2024)
The use of safe cosmetics has become an important concern among Indonesian society, especially with the rise of illegal cosmetic products containing hazardous materials such as mercury and hydroquinone. This community service activity aims to increase the knowledge of the Kopelma Darussalam Village community regarding safe cosmetics through education about the